2021
DOI: 10.3390/axioms11010017
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Evaluation Methodology for Mining Association Rules

Abstract: At present, association rules have been widely used in prediction, personalized recommendation, risk analysis and other fields. However, it has been pointed out that the traditional framework to evaluate association rules, based on Support and Confidence as measures of importance and accuracy, has several drawbacks. Some papers presented several new evaluation methods; the most typical methods are Lift, Improvement, Validity, Conviction, Chi-square analysis, etc. Here, this paper first analyzes the advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It optimizes the measurement of connection tightness of network structure and adds the calculation of asymmetric interaction intensity and the matching degree of personality link preference to the social relationship prediction model, which improves the model’s accuracy. In the future, research results can be applied to various fields, including personalized recommendation ( Xu et al, 2020 , 2021a , b ; Bao et al, 2022 ), sustainable tourism ( Xiang et al, 2021 ; Wang et al, 2022 ), personal health ( Tang Z. et al, 2021 ), and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It optimizes the measurement of connection tightness of network structure and adds the calculation of asymmetric interaction intensity and the matching degree of personality link preference to the social relationship prediction model, which improves the model’s accuracy. In the future, research results can be applied to various fields, including personalized recommendation ( Xu et al, 2020 , 2021a , b ; Bao et al, 2022 ), sustainable tourism ( Xiang et al, 2021 ; Wang et al, 2022 ), personal health ( Tang Z. et al, 2021 ), and so on.…”
Section: Discussionmentioning
confidence: 99%
“… Mo et al (2022) proposed a deep learning framework for temporal network link prediction. Bao et al (2022) proposed an improved evaluation methodology for association rules and link prediction. Wei et al (2022) proposed a novel time series-based graph model with text, called text with time series for graph (TT-Graph) model, which explicitly considers the user similarity and time series similarity.…”
Section: Related Workmentioning
confidence: 99%
“…From the perspective of research innovation ( 35 38 ), countries with strong innovation in carbon neutrality research are the United States, Australia, Germany, Japan, France, and other developed countries, and one institution with strong innovation is Univ Toronto (Canada). It is found that these countries and institutions lead the development of global carbon neutrality.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon makes the data tracing pressure of the full node surge in the sales season, which we call the consumer-level-traceability request pressure. Instead of focusing on professional data, consumers pay more attention to visual data such as images and videos with a strong presentation [15][16][17]. This paper aims to solve the pressure of consumer-level traceability and meet the needs of consumers, using the image evidence as a means of enhancement to build a consumer-level-traceability system based on blockchain technology.…”
Section: Introductionmentioning
confidence: 99%